AI for social good - Lim, Yuh Horng (Nanyang Technological University, 2023)
Suicide is a prevalent global issue that affects people of all ages and regions, with 703,000 people taking their own life every year. Suicide is a tragic event that not only impacts individuals but also has lasting effects on their loved ones. Globally, suicide is the fourth leading cause of death among 15–29-year-olds. With the recent development in machine learning and prevalence of social media, it warrants a further exploration in this problem.